DGAT1 mutations leading to delayed chronic diarrhoea: a case report - Luojia Xu; Weizhong Gu; Youyou Luo; Jingan Lou; Jie Chen (BMC, 2020)
Abstract Background Early-onset chronic diarrhoea often indicates a congenital disorder. Mutation in diacylglycerol o-acyltransferase 1 (DGAT1) has recently been linked to early-onset chronic diarrhoea. To date, only a few cases of DGAT1 deficiency have been reported. Diarrhoea in those cases was severe and developed in the neonatal period or within 2 months after birth. Case presentation Here, we report a female patient with DGAT1 mutations with delayed-onset chronic diarrhoea. The patient had vomiting, hypoalbuminemia, hypertriglyceridemia, and failure to thrive at early infancy. Her intractable chronic diarrhoea occurred until she was 8 months of age. A compound heterozygous DGAT1 mutation was found in the patient, which was first found in the Chinese population. Her symptoms and nutrition status improved after nutritional therapy, including a fat restriction diet. Conclusions This case expanded our knowledge of the clinical features of patients with DGAT1 mutations. Intractable diarrhoea with delayed onset could also be a congenital disorder.